La gestión crediticia y la liquidez de la Cooperativa de Ahorro y Crédito Ecuafuturo de la ciudad de Ambato. - Auquilla Quishpi, Nataly Mishell (2025)
The present research aimed to determine the credit management and liquidity of the Ecuafuturo Savings and Credit Cooperative, located in the city of Ambato. To achieve this, a hypothetical–deductive methodology was applied, using a descriptive approach and a non-experimental design. A sample of eight cooperative members currently employed at the institution was selected to gain a clearer understanding of how credit management and liquidity operate within the cooperative. Additionally, a Likert-scale survey was administered as part of the data collection process. Data analysis was performed using Cronbach’s alpha to assess the reliability of the survey, and the Chi-square test was used to test the hypothesis, with Excel and SPSS as the primary tools. The findings indicated that effective credit management plays a crucial role in maintaining adequate liquidity to meet customer demands. Key aspects of successful credit management include building trust between staff and customers and ensuring transparency regarding credit transaction procedures. The study also highlights the need to enhance communication strategies to better inform customers about the cooperative’s services. Understanding both credit management and liquidity provides valuable insights into the factors essential for the cooperative’s growth. Customer acquisition and retention, supported by effective management and tailored liquidity options, are fundamental to adapting to technological and social changes.